Tackling terrorism in Britain: threats, responses, and challenges twenty years after 9/11 - Greer, Steven (Routledge research in terrorism and the law, 2022)
Themes and trends -- Global jihad -- Domestic terrorism -- Protect and prepare -- Prevent -- Pursue -- Threats, responses, and challenges.